Comparing the activity level of salivary matrix metalloproteinase‐8 in patients with diabetes and moderate to severe chronic generalized periodontitis - Fatemeh Tavakoli; Masoumeh Faramarzi; Sepideh Salimnezhad; Bahare Jafari; Hosein Eslami; Bardia MohammadPourTabrizi (Wiley, 2024)
Abstract Objectives The response of the host to plaque can be affected by systemic diseases like diabetes, hormonal changes, or immunological deficits, which can hasten the progression and severity of periodontitis. This study aimed to compare the activity of salivary matrix metalloproteinase‐8 (MMP‐8) in patients with moderate to severe generalized chronic generalized periodontitis between healthy individuals and those with type 2 diabetes who were referred to the Tabriz School of Dentistry. Materials and Methods For this cross‐sectional study, 90 patients were randomly divided into three groups based on inclusion and exclusion criteria: patients with chronic generalized periodontitis with diabetes, patients with generalized chronic periodontal disease with normal blood glucose, and a control group of 30 healthy individuals. Participants were instructed not to brush their teeth for 12 h and not to eat or drink for 90 min before saliva sampling. Saliva samples were immediately stored at −80°C and analyzed using an ELISA test. Results The results showed that there was a significant difference in salivary MMP‐8 levels among the three groups. Patients with periodontitis and diabetes had the highest levels of salivary MMP‐8, while the control group had the lowest levels. This indicates that chronic generalized periodontitis is strongly associated with the activity level of salivary MMP‐8, and elevated levels of MMP‐8 in diabetic patients demonstrate the impact of diabetes on periodontal disease. Conclusion This study highlights the importance of monitoring salivary MMP‐8 levels in patients with periodontitis, especially those with diabetes. It also emphasizes the need for proper management of systemic diseases to prevent or slow down the progression of periodontal disease.